Implementasi Progressive Web Application dan Framework CodeIgniter pada Sistem Informasi Lomba Karya Tulis Ilmiah Mahasiswa - Anarya Indika Putra; Agi Putra Kharisma; Novanto Yudistira (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The efficiency and effectiveness of information dissemination and communication are becoming increasingly important today. Centralization of dispersed information to cut effort and time is one way to streamline and make communication and information dissemination more effective. The centralization of information can be applied to the field of student scientific writing competitions by creating an Information System for Student Scientific Writing Contest which acts as an information center. The information center is developed in the form of a web because it is versatile and the development process will be more efficient. CodeIgniter framework and progressive web application (PWA) are implemented on the developed system. The lightweight CodeIgniter framework assisted by the use of caching in PWA is expected to provide good performance in terms of page load time. The versatility of web-based systems will be optimized by implementing PWA that allows native application features to be implemented. In this study, performance testing was carried out to provide an overview of system performance. This study produces a web-based system that implements the CodeIgniter and PWA frameworks with 100% validity in unit testing, integration, and validation. Performance tests show performance gains and losses against various page load time metrics. Performance metrics of the first byte, first contentful paint, speed index, and document complete time improve on first and repeat visits. The performance of the fully-loaded time metric increases on the first visit and decreases on repeat visits.